(untitled) (Research, Society and Development, 2023)
Self-medication is the selection of medicines by the individual to treat diseases and symptoms that are recognized by him/herself. The consequence of self-medication can be irreversible, providing the individual with organ problems such as kidney failure, increased diabetes, heart failure. This study aims to analyze the profile of self-medication among employees of one of the branches of a supermarket chain located in the city of Gurupi Tocantins, with the aim of promoting knowledge about the irrational use of medicines among these employees. This study is configured as a descriptive exploratory study, with a qualitative and quantitative approach, where a questionnaire was applied with the help of the researcher, which contains a number of questions that are not considered too extensive, favoring patient adherence who will be able to respond in the same way. way you find most comfortable. The result of the research has a total of 106 employees interviewed, 52 women (73%) and 19 men (27%), where it was evidenced that the female gender makes more use of self-medication. In the data analysis, 61 of the participants used medication in the last 6 months and 42 were not prescribed by a pharmacist or doctor. And the main causes reported for self-medication were 68% lack of time to go to an appointment and 23% having been previously treated with the same medication. To ensure that the patient has adequate access to their treatment, Pharmaceutical Care emerges as a tool to provide effective drug treatment, avoiding self-medication.